Síntese, caracterização e estudos luminescentes de novos híbridos orgânico-inorgânicos: complexos de Eu(III), Tb(III) e Gd(III) com ligantes 1,3-dicarbonílicos não usuais - Larissa Alves Correa (2017)
Eu (III) and Tb (III) coordination compounds with 1,3-dicarbonyl ligands (RCOCH2COR) present very important applicability in photoelectronic devices. The development of these new complexes with enhanced physicochemical properties for devices with higher efficiency and lower cost is essential. The rational planning of promising novel photoluminescent agents by the synthesis of bis-functionalised molecular hybrid derivatives as specific building blocks with ever well-known fluorescent subunits is the key-step for the synergism of physicochemical and pho-tophysical properties. In the case of organic-inorganic molecular hybrids, the high electrolumi-nescent efficiency and specificity of the physicochemical properties of some lanthanides (Eu and Tb, among others) can be coupled with the high conjugation and electron-donating ability from some high fluorescent organic compounds as ligands for the investigation of novel deriva-tives. In the literature, there is a few investigation about the complexes of metals of the block d and f with 1,3-diketonic ligands from 3-acetyl-thiophene and 1,3-monocarbonyl-monoamide and 1,3-diamides; thus forming complexes that may exhibit greater thermal and / or chemical stabil-ity, with improved physicochemical properties for greater applicability in photoelectronic devices. The present work shows the attempts of 1,3-dicarbonylic thiophene compounds prepara-tion and the successful synthesis of substituted aromatic,3-monocarbonyl-monoamide and 1,3-diamide compounds with characterization by usual spectrometric techniques: Nuclear mag-netic resonance and carbon spectroscopy, infrared, ultraviolet, visible spectroscopy, and high-resolution mass spectrometry. These compounds were also studied as ligands for coordination studies with lanthanides metals: europium, terbium and gadolinium. The complexes presented in this work are unpublished and with the general structure [Ln(1,3-carbonyl)3]Cl3, with 1,3-monocarbonyl-moamide and 1,3-diamides as ligands; it has been suggested that these com-pounds may be coordinated by the carboxyl-amidic oxygen atoms or by the nitrogen ones. The complexes were characterized by thermogravimetry, infrared and ultraviolet-visible spectrosco-pies and fluorescence. It is noteworthy that these novel coordination compounds presented high fluorescence, the 1,3-diamide congeners showed higher decay times and the investigation of the luminescent properties allowed some suggestions about the molecular structure. These stimulating results and the normal expected thermal stability corroborated the promising ap-plicability of these novel complexes for utilization in optoelectronic devices.